Implementación de ejercicios para escoliosis funcional en soldados del Batallón Girardot (2015)
The study comes as a need to analyze the presence countless back pain in soldiers of the battalion Girardot, which are subjected to long hours of training where they bear the weight of the baggage of between 30- 40 kg, in addition to its hours of rest in the front lines can become quite narrow and uncomfortable, where they must take some ergonomic postures for a few hours resting places. As previously discussed it could analyze that one of the problems of greatest increase in this battalion are specifically functional scoliotic type, so I wanted through two different rehabilitation techniques Schroth and Klapp correct these deformities, individually analyzing progress with each technique to the end of the intervention show that technical best results were achieved. This study was conducted with four soldiers of this battalion who through informed consent they gave their permission for the application of techniques and decision of the photographic record as evidence of the procedure performed. Two groups were formed each with two soldiers, where the first group A work technique Schroth and the second group B with the technique Klapp, where physiotherapy was performed twice weekly for four weeks with an intensity hour per session in which four exercises per session for both techniques were performed. After four weeks was carried out analyzing the results of intervention where it was shown that both techniques are effective in the treatment of scoliosis, but comparing the technique Schrote with the technique Klapp first introduced better in patients with functional scoliosis.